2022
DOI: 10.1001/jamapediatrics.2022.2313
|View full text |Cite
|
Sign up to set email alerts
|

Global Changes in Child and Adolescent Physical Activity During the COVID-19 Pandemic

Abstract: IMPORTANCE Numerous physical distancing measures were implemented to mitigate the spread of the COVID-19 virus, which could have negatively affected child and adolescent physical activity levels.OBJECTIVES To conduct a systematic review and meta-analysis of the literature that used validated measures to document changes in child and adolescent physical activity during the COVID-19 pandemic and to estimate whether changes in physical activity differed between participant-level, contextual, and methodological mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 77 publications
8
90
2
2
Order By: Relevance
“…Reducing gender inequalities is an important aim of global physical activity strategies, 25 and the present study suggests that gender inequality was a significant moderator of trends in most of the indicators. An analysis of Global Matrix 4.0 data 22 shows that physical activity indicators declined globally as a result of COVID-19 pandemic mitigation measures, consistent with other evidence, 26,27 but the influence of COVID-19 on the trends analyzed in the present study was relatively minor because data collection for GM 4.0 occurred prior to the COVID-19 pandemic for most report card indicators in most countries. 22…”
Section: Main Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…Reducing gender inequalities is an important aim of global physical activity strategies, 25 and the present study suggests that gender inequality was a significant moderator of trends in most of the indicators. An analysis of Global Matrix 4.0 data 22 shows that physical activity indicators declined globally as a result of COVID-19 pandemic mitigation measures, consistent with other evidence, 26,27 but the influence of COVID-19 on the trends analyzed in the present study was relatively minor because data collection for GM 4.0 occurred prior to the COVID-19 pandemic for most report card indicators in most countries. 22…”
Section: Main Findingssupporting
confidence: 89%
“…Our findings suggest that across the 4 Global Matrix initiatives (published between 2014 and 2022) time spent in physical activity and sedentary behaviors among children and adolescents globally, and the influences on these behaviors, were relatively stable, though for most of the report card indicators trends were more undesirable in countries with higher levels of gender inequality. If the global goal to reduce physical inactivity in adolescents by 15% by 2030 27 is to be met, the present study suggests that more urgent and substantial actions will be required in the rest of this decade. If global ambitions to reduce gender inequalities in physical activity among children and adolescents are to be achieved 25 , the present study also suggests more urgent and more substantive attention is required.…”
Section: Discussionmentioning
confidence: 87%
“…These findings should be considered along with another meta-analysis suggesting a 32% decrease in children's engagement in moderate to vigorous physical activity during the pandemic. 74 Policy-relevant pandemic recovery planning and resource allocation should therefore consider how to help children, adolescents, and families to "sit less and play more" to meet the 24-hour movement guidelines. 75 In this meta-analysis, we identified several moderators that explained existing heterogeneity across studies examining changes in screen time before vs during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity and sedentary behaviors have adverse consequences on physical fitness levels [10]. Many research studies from different countries showed a worrying decrease of physical activity levels (PAL), associated to a dramatic increase of time spent in sedentary behaviors during and after lockdown [11,12]. The authors stated that social context, parental education level, environment and physical characteristics are factors having an impact on the percentage of decrease in PAL during lockdown [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%